PERLINDUNGAN HUKUM TERHADAP DOKTER DALAM PEMBUKAAN REKAM MEDIK PASIEN HUMAN IMMUNODEFICIENCY VIRUS/ACQUIRED IMMUNODEFICIENCY SYNDROME (HIV/AIDS) - Siti Handayani (Jurnal Idea Hukum, 2018)
ABSTRACTThis study aims to 1) to describe, identify and analyze physicians' authority in opening medical records of HIV / AIDS patients; and 2) to analyze and solve legal protection problems for physicians in opening medical records on HIV / AIDS patients. This study uses the legislation approach. The data obtained from interviews with Director of RSUD Majenang, Counselor of HIV / AIDS and doctors responsible for poly / AIDS RSUD Majenang. The data of the research are analyzed using deductive method. Based on the results of research and discussion, the conclusions are as follows: First, the authority of doctors in opening medical records of HIV / AIDS patients is set in Permenkes RI number 269 / MENKES / PER / III / 2008 and number 36 of 2012 on the Secret of Medicine that is only for the sake of health patient, fulfilling the request of the law enforcement apparatus in the context of law enforcement on the order of the court which must be requested in writing to the leader of the health service facility, the request and / or consent of the patient himself, the request of the institution / institution based on the provisions of the legislation as well as for the interest of research, education and medical audit as long as it does not mention the identity of the patient, as well as a condition that threatens the safety of others individually and society. Individuals in question is the person most potentially infected HIV / AIDS ie wife or husband of HIV / AIDS. Secondly, legal protection in opening medical records in HIV / AIDS patients is administered by the government in a preventive manner aimed at preventing the occurrence of disputes, leading to prudent action in the presence of various provisions set forth in the medical practice, health and health minister regulations . Protection of repressive legal protection in the event of a violation in the practice of medical services aimed at handling a particular dispute which is also regulated in the Criminal Code and legislation to ensure that physicians and patients obtain their rights and obligations in accordance with applicable laws and regulations.Keywords: Legal protection, HIV / AIDS